A technical protocol for an experimental ex vivo model using arterially perfused porcine eyes. (April 2019) - Rousou, C.; Hoogenboom, P.; van Overdam, K.A.; Storm, G.; Dorrestijn, J.; Mastrobattista, E.
Abstract: Ex vivo ocular perfused models have been described in the past and were applied in different mammalian species as platforms to test drug delivery systems and surgical techniques. However, reproduction of those methods is challenging because extensive and precise description of the protocols used is lacking. In this technical paper we provide a detailed description of all the steps to be followed from the enucleation of porcine eyes to cannulation of the ophthalmic artery and perfusion. This model can contribute to the reduction of use of living animals in ophthalmology research, whereas as opposed to in vitro models, it preserves tissue complexity and integrity.